2006
DOI: 10.1021/jp063644n
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Measuring the Size of Metal Nanoclusters in Solution

Abstract: The connection between quantum size effects and the surface plasmon resonance of metal nanoclusters is introduced and the pros and cons of in situ and ex situ cluster analysis methods are outlined. A new method for estimating the size of nanoclusters is presented. This method combines core/shell cluster synthesis, UV-visible spectroscopy, and Mie theory. The core/shell approach enables the estimation of metal cluster sizes directly from the UV-visible spectra, even for transition metal nanoclusters such as Pd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…(i) It is destructive: the sample can be analyzed only once; (ii) It can be performed only with dry, solid samples; it is not suitable for in situ analyses; (iii) The three-dimensional description of the particle is only a reconstruction of two-dimensional images, based on the observation of a set of particles and presuming their random orientation [19]. In addition to microscopy methods, DLS is also employed widely to measure the sizes of metal particles [20]. Although DLS can be used to rapidly measure the sizes of NP products, it is difficult to infer the properties of an ensemble of NPs, such as their physical properties (e.g., absorbance), using this approach [21].…”
Section: Introductionmentioning
confidence: 99%
“…(i) It is destructive: the sample can be analyzed only once; (ii) It can be performed only with dry, solid samples; it is not suitable for in situ analyses; (iii) The three-dimensional description of the particle is only a reconstruction of two-dimensional images, based on the observation of a set of particles and presuming their random orientation [19]. In addition to microscopy methods, DLS is also employed widely to measure the sizes of metal particles [20]. Although DLS can be used to rapidly measure the sizes of NP products, it is difficult to infer the properties of an ensemble of NPs, such as their physical properties (e.g., absorbance), using this approach [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since Li 26 reported the geometrical structures of ground state Ag n (n=2-20) clusters performed by Density Functional Theory (DFT) based at two levels with exchange-correlation functional by PW91 and combined with LANL2DZ basis set, which indicated that the turnover point from 2 dimension to 3 dimension for geometrical structures of Ag nanoparticles occurred at the size of Ag 8 as shown in Figure 4, the increase in size of the prepared Ag n nanoparticles at n=5-8 with the increase of Ag atoms was larger than that at n>10, because of the smaller efficiency of space filling. Meanwhile, the size of prepared Ag n nanoparticles (n= 5-30) was much smaller than the 4.5 nm diameter of G5.0 PAMAM dendrimers, 27 showing the nanoparticles may locate inside the dendrimer frame. And according to a previous study, 28 G5.0-OH PAMAM dendrimers are known to be very strong and stable capping agents of noble metal nanoparticles.…”
Section: Resultsmentioning
confidence: 92%
“…6B shows that different MRs of the Au@P1 systems correspond to different absorption wavelengths, suggesting that the gold nanoparticles have different sizes. 11,60 In addition, we found that there is no obvious absorption at 520 nm for Au@P1 with MR ¼ 1/30, which may be attributed to the formation of smaller gold nanoclusters. 61 The specic size and morphology of Au NPs@P1 with different MRs can be obtained from the TEM images in Fig.…”
Section: Synthesis Of Block Copolymer-stabilized Au Npsmentioning
confidence: 78%
“…[1][2][3][4] Noble metal nanoparticles (NPs) made of gold, platinum, etc., due to their valuable optical and catalytic properties, have been widely used in catalysis, optoelectronic devices and biomedicine. [5][6][7][8][9][10][11] Especially, gold nanoparticles (Au NPs) have attracted a lot of attention due to their unique properties, which may markedly differ from those of the respective bulk metal. 12 Au NPs are the most stable metal nanoparticles and they exhibit unique properties, such as size-related electronic, magnetic, and optical properties.…”
Section: Introductionmentioning
confidence: 99%